2022
DOI: 10.3390/polym14153215
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experiments and Numerical Simulation Study of Composite-Material-Modified Loess Improving High-Speed Railway Subgrade

Abstract: Construction of high-speed railway subgrade on loess soils in the Loess Plateau is risky because such soil is susceptible to differential settlements. Various soil-improvement methods have been used to enhance the mechanical properties of loess. Lime-ash soil and cement-lime soil are the most commonly used methods in the improvement of loess subgrade, while few studies have been found on loess subgrade improvement by using composite material consisting of traditional materials and new materials. A series of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Large loess covers lie in China. Analyses including FEM calculations for the improved loess subsoil were presented in [71]. The subsoil was improved due to the collapsing nature of loess.…”
Section: Discussionmentioning
confidence: 99%
“…Large loess covers lie in China. Analyses including FEM calculations for the improved loess subsoil were presented in [71]. The subsoil was improved due to the collapsing nature of loess.…”
Section: Discussionmentioning
confidence: 99%
“…to control the compactness and stability of subgrade filling. At the same time, polymers, geotextiles and geogrids can be added to the subgrade fill to reduce the differential settlement deformation of the transition section [13][14][15][16][17][18] . These methods can have a significant effect on the differential settlement control of bridge-subgrade transition sections in collapsible loess areas.…”
Section: And Weiwei Wumentioning
confidence: 99%
“…Bai et al 22 used a collapsibility test, gray relational analysis, and unconfined compressive strength test to study calcium lignosulfonate-modified loess's collapsibility and mechanical properties. Luo et al 23 conducted direct shear tests and unconfined compression tests by adding cement, polypropylene fibers, and loess samples of SCA-2 soil stabilizer composites and found that the compressive strength indexes of modified loess had a significant impact on foundation settlement. Cheng et al 24 proposed using microorganism-induced calcium carbonate deposition technology to modify loess mechanical performance.…”
Section: Introductionmentioning
confidence: 99%